"A theater of new, unforeseen constellations": Walter Benjamin's "Arcade" in postcolonial theories of (cultural) translation. Issue 1 (2nd January 2023) - Haberpeuntner, Birgit
ABSTRACT: In 1921, Walter Benjamin wrote his well-known essay about translation, "Die Aufgabe des Übersetzers". Today, this text has become a classic reference in a broad spectrum of discussions within the fields of cultural and translation theory, often subsumed under the heading of "cultural translation". This article examines how Benjamin's essay has found its way into this discourse by looking at two exemplary texts from the field of postcolonial studies, namely Tejaswini Niranjana's Siting Translation and Rey Chow's Primitive Passions . The starting point for this investigation is a disturbance in translation: tracing the interlingual discrepancies of a single word that has become emblematic of Benjamin, namely the "arcade", this text not only illustrates lines of dis/continuation between Benjamin's writings and postcolonial perspectives on (cultural) translation, but also demonstrates how these new, English-language theorizations re-shape Benjamin's texts, disturbing, shifting and enriching their more "traditional" readings.